On the sensitivity of weak gravitational lensing to the cosmic expansion function - Schmidt, Christian F.; Bartelmann, Matthias (Monthly notices of the Royal Astronomical Society, 2024)
We analyse the functional derivative of the cosmic-shear power spectrum $C_\ell ^γ$ with respect to the cosmic expansion function. Our interest in doing so is two-fold: (i) In view of attempts to detect minor changes of the cosmic expansion function that may be due to a possibly time-dependent dark-energy density, we wish to know how sensitive the weak-lensing power spectrum is to changes in the expansion function. (ii) In view of recent empirical determinations of the cosmic expansion function from distance measurements, independent of specific cosmological models, we wish to find out how uncertainties in the expansion function translate to uncertainties in the cosmic-shear power spectrum. We find the following answers: relative changes of the expansion function are amplified by the cosmic-shear power spectrum by a factor ≈2-6, weakly depending on the scale factor where the change is applied, and the current uncertainty of one example for an empirically determined expansion function translates to a relative uncertainty of the cosmic-shear power spectrum of $≈ 10~{{\ \rm per\ cent}}$.